2019
DOI: 10.1007/s12040-019-1070-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term (2005–2012) measurements of near-surface air pollutants at an urban location in the Indo-Gangetic Basin

Abstract: Simultaneous long-term measurements of near-surface air pollutants at an urban station, New Delhi, were studied during 2005-2012 to understand their distribution on different temporal scales. The annual mean mass concentrations of nitrogen dioxide (NO 2), sulphur dioxide (SO 2), particulate matter less than 10 µm (PM 10) and suspended particulate matter (SPM) were found to be 62.0 ± 27.6, 12.5 ± 8.2, 253.7 ± 134 and 529.2 ± 213.1 µg/m 3 , respectively. The 24-hr mean mass concentrations of NO 2 , PM 10 and SPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 58 publications
0
6
1
Order By: Relevance
“…Data pertaining to air pollutants was obtained from the Delhi Pollution Control Committee (DPCC) at the residential site, Ashok Vihar in Delhi. A population density map of Delhi is shown recently by Kishore et al (2019) using 2011 Census data. As per the map, the present measurement site is situated in a densely populated locality in the North-West direction of Delhi, which is well connected through roads and public transport.…”
Section: Measurement Site and Experimental Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data pertaining to air pollutants was obtained from the Delhi Pollution Control Committee (DPCC) at the residential site, Ashok Vihar in Delhi. A population density map of Delhi is shown recently by Kishore et al (2019) using 2011 Census data. As per the map, the present measurement site is situated in a densely populated locality in the North-West direction of Delhi, which is well connected through roads and public transport.…”
Section: Measurement Site and Experimental Detailsmentioning
confidence: 99%
“…O 3 was measured using chemiluminescence method. More details of the measurements of these air pollutants along with their detection range and uncertainties are discussed by Kishore et al (2019) .…”
Section: Measurement Site and Experimental Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…At that PM 2.5 and PM 10 concentrations demonstrate the similar tendencies in their formation. As PM 10 increases, PM 2.5 also increases (Kishore et al 2019); thus, on 15 May 2019 the whole territory of the South Gobi experienced a dust storm of various intensity with maximum concentrations in Wuwei (PM 10 1582 μg/m 3 PM 2.5 468 μg/m 3 ), Zhangye (PM 10 1040 μg/m 3 and PM 2.5 356 μg/m 3 ), and Zhongwei (PM 10 729 μg/m 3 and PM 2.5 232 μg/m 3 ), suggesting similar sources of aerosols formation. However, the dust event did not influence the change in NO 2 , SO 2 , and CO, which were 14, 9, and 12 μg/m 3 (for NO 2 ); 4, 4, and 8 μg/m 3 (for SO 2 ); 0.2, 0.2, and 0.4 mg/m 3 (for CO) for Wuwei, Zhangye, and Zhongwei, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, in winter, Alashan is subject to the influence of emissions from fossil fuel burning (coal for heating) to an even greater degree than other cities, leading to high PM 2.5 /PM 10 ratio (December 0.58, January 0.61, February 0.56, with average seasonal value 0.58). The higher PM 2.5 /PM 10 ratios may also be attributed to vehicles emissions and secondary particles, formed through photochemical processes at high temperatures (Kishore et al 2019), while lower ratios in most scenarios are associated with violent sand and dust emissions from nearby deserts (Zhang 2016). Upon analysis of PM 2.5 /PM 10 ratio results obtained, it may be concluded that the main pollutant of all the cities of the region is coarse particles.…”
Section: Seasonal Variations In Atmospheric Pollutantsmentioning
confidence: 99%